Assessment of Maternal Satisfaction and Associated Factors among Parturients Who Underwent Cesarean Delivery under Spinal Anesthesia at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2019. (12th October 2020) - Bayable, Samuel Debas; Ahmed, Seid Adem; Lema, Girmay Fitiwi; Yaregal Melesse, Debas
Abstract : Background . Spinal anesthesia is the most common anesthetic technique for cesarean delivery. Patient satisfaction is a subjective and complicated concept, involving physical, emotional, psychological, social, and cultural factors. Regular evaluation of maternal satisfaction related to anesthesia service is an important parameter to the required changes and expansion of high-quality care services. We aimed to assess maternal satisfaction and associated factors among parturients who underwent cesarean delivery under spinal anesthesia. Methods . Institutional-based cross-sectional study was conducted from February to May 2019. A total of 383 parturients were enrolled to assess maternal satisfaction using a 5-point Likert scale. Both bivariable and multivariable logistic regression analyses were done. Variables of p value ≤0.2 in the bivariable analysis were a candidate for multivariable logistic regression. A p value <0.05 was considered as significantly associated with maternal satisfaction at 95% CI. Results . This study revealed that 315 (82.3%) of the parturients were satisfied. Single spinal prick attempts (AOR = 2.08, 95% CI = 1.05–4.11), successful spinal block (AOR = 7.17, 95% CI = 3.33–15.43), less incidence of postdural puncture headache (AOR = 2.36, 95% CI = 1.33–4.20), and prophylactic antiemetic use (AOR = 0.35, 95% CI = 0.19–0.66) were positively associated with maternal satisfaction. Conclusions . The overall maternal satisfaction receiving spinal anesthesia was considerably low. Single spinal prink attempts, successful spinal block, and less incidence of postural puncture headache can increase maternal satisfaction. Therefore, effective perioperative management, skillful techniques, and using the small-gauge Quincke spinal needle (25–27 gauge) may increase the maternal satisfaction and quality of spinal anesthesia management.